2020
DOI: 10.1088/2053-1591/ab677c
|View full text |Cite
|
Sign up to set email alerts
|

Texture-tensile properties correlation of 304 austenitic stainless steel rolled with the change in rolling direction

Abstract: Rolling, at elevated temperature, with a change in the rolling direction (RD) have been conducted on 304 austenitic stainless steel. Two different sequences of change in RD, after each pass, have been followed viz., change in RD by 90°; designated as cross rolling (CR) and change in RD by 180°; designated as reverse rolling (RR). Effect of this change in RD on texture and tensile properties has been studied through Electron backscattered diffraction (EBSD) and uniaxial tensile test, respectively. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The yield point occurs at a high stress [19], and the yield strengths and elongation at fracture in both directions were almost similar; however, the tensile strength was slightly higher in the TD, by approximately 45 MPa. It is a well-known fact that texture can have a significant impact on tensile properties [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The yield point occurs at a high stress [19], and the yield strengths and elongation at fracture in both directions were almost similar; however, the tensile strength was slightly higher in the TD, by approximately 45 MPa. It is a well-known fact that texture can have a significant impact on tensile properties [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Han et al [ 12 ] reported that the yield strength and the impact toughness of the samples along the rolling direction (RD) were higher than that of the samples along the transverse direction (TD) in 316 L stainless steel. Rout [ 13 ] analyzed the effect of texture on the anisotropic behavior of tensile properties based on the Taylor factor values in 304 stainless steel. Unfortunately, these investigations were performed at room temperature only and did not analyze the differences in mechanical properties based on the microstructural evolutions by deformation.…”
Section: Introductionmentioning
confidence: 99%